Problem Solving Skill Seen from Adversity Quotient through Problem Based Learning Assisted by E-Comic Math - NALURITA, BERNIKA RAHMANIA; WALID, WALID; Cahyono, Adi Nur (Universitas Negeri Semarang, 2021)
This research aimed to describe problem solving skill of students seen from adversity quotient through Problem Based Learning assisted by E-Comic Math. This mixed method research used sequential explanatory design with 23 subjects taken from VII A4 class at Islamic JHS Sultan Agung 4, Semarang, selected based on three adversity quotient categories: quitter, camper, and climber. The techniques of collecting quantitative data were problem solving test and adversity quotient questionnaire. The qualitative data collecting techniques were based on interview and adversity quotient questionnaire results and problem solving skill test. The findings showed that Problem Based Learning assisted by E-Comic Math was effective and the description of problem solving skill seen from the students’ adversity quotient based on three categories through Problem Based Learning assisted by E-Comic were different. They were shown by quitter student category reached good and sufficient levels of problem solving skill. The camper students reached excellent, good, and sufficient levels. The climber students reached excellent and good levels of problem solving skills.